Role of CD40 and ADAMTS13 in von Willebrand factor-mediated endothelial cell-platelet-monocyte interaction - Popa, Miruna-Andrea; Leuschner, Florian; Bugert, Peter; Wagner, Andreas H.; Hecker, Markus (Proceedings of the National Academy of Sciences of the United States of America, 2018)
Monocyte extravasation into the vessel wall is a key step in atherogenesis. It is still elusive how monocytes transmigrate through the endothelial cell (EC) monolayer at atherosclerosis predilection sites. Platelets tethered to ultra-large von Willebrand factor (ULVWF) multimers deposited on the luminal EC surface following CD40 ligand (CD154) stimulation may facilitate monocyte diapedesis. Human ECs grown in a parallel plate flow chamber for live-cell imaging or Transwell permeable supports for transmigration assay were exposed to fluid or orbital shear stress and CD154. Human isolated platelets and/or monocytes were superfused over or added on top of the EC monolayer. Plasma levels and activity of the ULVWF multimer-cleaving protease ADAMTS13 were compared between coronary artery disease (CAD) patients and controls and were verified by the bioassay. Two-photon intravital microscopy was performed to monitor CD154-dependent leukocyte recruitment in the cremaster microcirculation of ADAMTS13-deficient versus wild-type mice. CD154-induced ULVWF multimer-platelet string formation on the EC surface trapped monocytes and facilitated transmigration through the EC monolayer despite high shear stress. Two-photon intravital microscopy revealed CD154-induced ULVWF multimer-platelet string formation preferentially in venules, due to strong EC expression of CD40, causing prominent downstream leukocyte extravasation. Plasma ADAMTS13 abundance and activity were significantly reduced in CAD patients and strongly facilitated both ULVWF multimer-platelet string formation and monocyte trapping in vitro. Moderate ADAMTS13 deficiency in CAD patients augments CD154-mediated deposition of platelet-decorated ULVWF multimers on the luminal EC surface, reinforcing the trapping of circulating monocytes at atherosclerosis predilection sites and promoting their diapedesis.
Gesehen am 08.05.2020